The Church in Africa as a peacemaker A Theology of peace building in Africa (Hekima Review, 2016)
The persistence of tensions, divisions, conficts and encroachments among nations, ethnics and ideologies in many African countries incite us to think deeply about the roots of such experience and to suggest at the same time a theology which is relevant to Africa, which is a response to the need of reconstruction of a broken Africa. e argument that this article advances is that, in response to the need of Africa, and following the insight given by the Second Synod of Africa (2009) which dealt with the questions of peace, justice and reconciliation, the Church in Africa is called to be peacemaker. For that, we are suggesting here a theological foundation of such mission of peace in an attempt to promote a reconciled Africa. We are not defending here a model of reconciliation in sense of a systematic and scientific activity to which we can apply strategy, technic and plan. However, we advocate for a type of reconciliation as a virtue coming from a spiritual experience, coming from commitment to Christ as a model. Our chief motive is to suggest some variables that we consider to be crucial in the process of peacebuilding from a theological perspective.